2020
DOI: 10.4314/ahs.v20i1.25
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of plasmodium, leptospira and rickettsia species in Northern Tanzania: a community based survey

Abstract: Background: The overlap of symptoms, geographic and seasonal co-occurrence of Plasmodium, Leptospira and Rickettsia infections makes malaria diagnosis difficult, increasing the chances of misdiagnosis. The paucity of data on the prevalence Plasmodium, Leptospira and Rickettsia infections contributes to an overly diagnosis of malaria. We aimed to determine the prevalence and distribution of Plasmodium, Leptospira and Rickettsia infections in northern Tanzania. Methods: A community based, cross sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…The studies showed, that besides malaria as expected, leptospirosis is also a potential cause of febrile illness, however, it is under-reported in comparison with malaria [ 32 , 42 , 57 ]. In addition, Leptospira infections were reported to be associated with contact with rodents and livestock (cattle, goats, and sheep).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies showed, that besides malaria as expected, leptospirosis is also a potential cause of febrile illness, however, it is under-reported in comparison with malaria [ 32 , 42 , 57 ]. In addition, Leptospira infections were reported to be associated with contact with rodents and livestock (cattle, goats, and sheep).…”
Section: Resultsmentioning
confidence: 99%
“…In some of the studies, other pathogens or conditions associated with fever were screened, such as Plasmodium spp. [ 17 , 31 , 32 , 35 , 57 ], Brucella , Rickettsia [ 32 , 35 , 55 , 62 ] and typhoid fever [ 31 , 35 ] for differential diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the human costs of malaria, billions of dollars are spent annually to control and eliminate malaria, representing a significant portion of governmental funding 46 . Importantly, patients diagnosed with malaria can also suffer from other infectious diseases as either super-infections or co-infections, which can enhance mortality rate [47][48][49] . We have demonstrated the role of inflammatory monocytes and monocyte derived dendritic cells in the pathogenesis of cerebral malaria and acute respiratory distress syndrome in rodent malaria models [50][51][52] .…”
Section: Discussionmentioning
confidence: 99%
“…There are more papers: chronic HIV infection and health related quality of life in resource poor settings 13 ; cryptococcosis among HIV patients in sub-Saharan Africa 14 ; malnutrition amongst HIV adult patients 15 ; viral suppression and low attrition in healthy HIV-infected patients initiated on ART with CD4 above 500 cells/µL 16 ; acceptance and utilization of HIV testing among the youth 17 ; rabies in Kwazulu-Natal 18 ; and central line-related bloodstream infections 19 . There are papers on Stenotrophomonas species 20 ; risk factors for trachoma in Burundi 21 ; plasmid-mediated resistance genes and multidrug-resistant uropathogens 22 ; prevalence of plasmodium , leptospira and rickettsia 23 ; seroepidemiology of human fascioliasis 24 ; Parvovirus B19 DNA detection in HIV anemic patients 25 ; safety of vaccines used in routine immunization in Africa 26 and distribution of genes among uropathogenic Escherichia coli and antimicrobial resistance 27 .…”
mentioning
confidence: 99%